Application of Index for Optimization Query Data in Graduate Information Systems - Agus Sifaunajah; Rosa Tarbiyatul Khusna (IJAIT (International Journal of Applied Information Technology), 2021)
Graduates from educational institutions within the foundation of the Bahrul Ulum Islamic Boarding School each year can be more than 1000 people. The potential for this critical data has not been supported by good data collection. The data collection process is still done manually. Therefore, the level of accuracy is still fragile. In this study, an index is applied to perform query optimization. The object of this research is the database of the graduate data information system at the Bahrul Ulum Islamic Boarding School Foundation. Data collection method using literature study and interviews. The experimental stage of this research is done by determining the target output by compiling query commands. Each query command is executed ten times to find the average execution time and runs on two different hardware platforms to determine the effect of hardware on the query process. The study results show that the index can be used for data query optimization but only if it is supported by good hardware specifications so that the command execution time is optimal. When only using the index application, the average difference in execution time is 0.5 seconds.